Screening of Antibiotic and Virulence Genes from Whole Genome Sequenced Cronobacter sakazakii Isolated from Food and Milk-Producing Environments - Ondrej Holý; Julio Parra-Flores; Jaroslav Bzdil; Adriana Cabal-Rosel; Beatriz Daza-Prieto; Ariadnna Cruz-Córdova; Juan Xicohtencatl-Cortes; Ricardo Rodríguez-Martínez; Sergio Acuña; Stephen Forsythe; Werner Ruppitsch (MDPI AG, 2023)
The objective of this study was to use whole-genome sequencing (WGS) to screen for genes encoding for antibiotic resistance, fitness and virulence in Cronobacter sakazakii strains that had been isolated from food and powdered-milk-producing environments. Virulence (VGs) and antibiotic-resistance genes (ARGs) were detected with the Comprehensive Antibiotic Resistance Database (CARD) platform, ResFinder and PlasmidFinder tools. Susceptibility testing was performed using disk diffusion. Fifteen presumptive strains of Cronobacter spp. were identified by MALDI-TOF MS and ribosomal-MLST. Nine C. sakazakii strains were found in the meningitic pathovar ST4: two were ST83 and one was ST1. The C. sakazakii ST4 strains were further distinguished using core genome MLST based on 3678 loci. Almost all (93%) strains were resistant to cephalotin and 33% were resistant to ampicillin. In addition, 20 ARGs, mainly involved in regulatory and efflux antibiotics, were detected. Ninety-nine VGs were detected that encoded for OmpA, siderophores and genes involved in metabolism and stress. The IncFIB (pCTU3) plasmid was detected, and the prevalent mobile genetic elements (MGEs) were ISEsa1, ISEc52 and ISEhe3. The C. sakazakii isolates analyzed in this study harbored ARGs and VGs, which could have contributed to their persistence in powdered-milk-producing environments, and increase the risk of infection in susceptible population groups.